Intentionality, Fitness and Evolution in William James’s Pragmatism - Baiardi, Daniel Cerqueira (Cognitio-Estudos: revista eletrônica de filosofia, 2012)
The purpose of this paper is to provide evidence of the outstanding participation of William James in what is understood as the Evolutionary Epistemology Research Program and his connections with this tradition. Via a rational reconstruction of the Jamesian project, I try to explain the direct influence of Herbert Spencer’s evolutionism on the development of his conception of mind and knowledge, surpassing even the well known influence of Darwin. Some authors hold that the procedural aspects and Jamesian evolutionary approach to the origin of mind is essentially Darwinist, but the similarities with Spencer’s system are diverse and meaningful. Although James accepts the correspondence theory, he suggests an omission by Spencer in accomplishing a real teleological analysis on individual interests. Stressing into the question of whether pleasure and pain have some relation with correspondence, he asserts that for a large number of elements in the environment, there should be a correlative neutral internal type, or intermediary, as a sense of reward. The evolutionary concept of fitness subsidizes a satisfactory interpretation to the Jamesian theory of knowledge. Understanding meaning as the conceivable effects of an object’s practical value, James holds the belief that truth is built through the process of an individual’s interaction with the world. This evolutionist’s assumption along with his naturalized notion of interest enables a fundamental theory of meaning – a necessary step to support his pragmatic conception of truth.